Risk Factors for Hypertension among Adult Patients Attending Nakuru County Teaching and Referral Hospital, Nakuru County, Kenya - Moimet Jelagat Winnie (Kabarak University, 2025)
Abstract Hypertension is a leading cause of cardiovascular morbidity and mortality globally and remains a growing public health concern in Kenya. Despite this, limited data exist on its determinants within urban outpatient settings such as Nakuru County. This study examined sociodemographic, lifestyle, and nutritional factors associated with hypertension among adult outpatients at Nakuru County Teaching and Referral Hospital. A descriptive cross-sectional design was used, involving 215 adults (≥18 years) attending the outpatient clinic. Participants were purposively selected and interviewed using a semi-structured questionnaire that captured sociodemographic characteristics, lifestyle behaviors, and dietary practices. Dietary intake was assessed using a food frequency questionnaire and a multistage 24-hour recall, while anthropometric measurements were obtained using standard procedures. Data were analyzed using descriptive statistics, chi square tests, and multivariable logistic regression at a 95% confidence level. Only 5.1% of participants had normal blood pressure, while 18.6% had elevated blood pressure, 52.6% Stage 1 hypertension, and 23.7% Stage 2 hypertension. After adjustment for potential confounders, older age, lifestyle behaviors, and excess adiposity were independently associated with hypertension. Adults aged 45–54 years (AOR = 2.67; 95% CI: 1.19–6.00) and those aged ≥55 years (AOR = 3.78; 95% CI: 1.59–8.99) had significantly higher odds of hypertension compared to adults <35 years. Alcohol use (AOR = 2.91; 95% CI: 1.32–6.44) and smoking (AOR = 2.67; 95% CI: 1.18–6.03) were significant behavioral predictors. Overweight, Class I and II obesity, and significantly increased waist circumference (AOR = 3.55; 95% CI: 1.78–7.07) were strong anthropometric predictors. Frequent salt addition during cooking and low vegetable intake were also significantly associated with elevated blood pressure. These findings highlight the need for targeted interventions in Nakuru County that prioritize screening for adults aged 45 years and above, promote weight and salt reduction, and address alcohol and tobacco use within routine hypertension management.
Full text
Keywords: Hypertension; Dietary Practices; Fruit And Vegetable Intake; Sodium– Potassium Balance; Kenya